Overexpression of ezrin and galectin-3 as predictors of poor prognosis of cervical cancer - Li,M. (2017)
The aim of this study was to explore the correlation of ezrin and galectin-3 expressions with prognosis in cervical cancer. The immunohistochemical method was applied to detect ezrin and galectin-3 expressions in normal cervix tissues (n=30), cervicitis tissues (n=28), cervical intraepithelial neoplasia (CIN) tissues (classified as I-III, n=89), and cervical carcinoma tissues (n=84). Follow-up was conducted for 5 to 78 months to analyze the correlation of protein expressions with prognosis. Ezrin and galectin-3 expressions in cervical cancer were significantly higher than in normal cervix, cervicitis and CIN (all P<0.05), and expressions in CIN were significantly higher than in normal cervix and cervicitis (both P<0.05). The expressions of ezrin and galectin-3 were both related with histological grade, deep myometrial invasion and lymph node metastasis (all P<0.05). Spearman analysis showed that ezrin expression was positively correlated with galectin-3 expression in cervical cancer (r=0.355, P<0.05). The survival rate of patients with high expressions of ezrin and galectin-3 was significantly lower than those with low expressions of proteins (both P<0.05). The expressions of ezrin and galectin-3, histological grade, depth of stromal invasion, and lymph node metastasis are risk factors affecting the survival rate of patients with cervical cancer. The expressions of ezrin and galectin-3 were correlated with the development of cervical cancer, and overexpressions of those proteins were indicative of poor prognosis in patients with cervical cancer.